2011
DOI: 10.1016/j.febslet.2011.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the pyoverdine siderophore of Pseudomonas aeruginosa involves precursors with a myristic or a myristoleic acid chain

Abstract: a b s t r a c tPyoverdine I (PVDI) is the major siderophore produced by Pseudomonas aeruginosa to import iron. Biosynthesis of this chelator involves non-ribosomal peptide synthetases and other enzymes. PvdQ is a periplasmic enzyme from the NTN hydrolase family and is involved in the final steps of PVDI biosynthesis. A pvdQ mutant produces two non-fluorescent PVDI precursors with a higher molecular mass than PVDI. In the present study, we describe the use of mass spectrometry to determine the structure of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(103 citation statements)
references
References 27 publications
9
94
0
Order By: Relevance
“…The molecular weight of purified pyoverdine was about 1278 (Fig. S7), which was similar with the previous researches [24,25]. The little difference was resulted from the variable peptide chain of pyoverdine, which could also be utilized as a fingerprint method to distinguish strains from each other [26].…”
Section: Pyoverdine Purificationsupporting
confidence: 86%
“…The molecular weight of purified pyoverdine was about 1278 (Fig. S7), which was similar with the previous researches [24,25]. The little difference was resulted from the variable peptide chain of pyoverdine, which could also be utilized as a fingerprint method to distinguish strains from each other [26].…”
Section: Pyoverdine Purificationsupporting
confidence: 86%
“…The mobile phase was acetonitrile to NaOH-acetic acid (17 mM, pH 5.3), with acetonitrile gradient ranged from 0% to 100% over 40 min at a flow rate of 1.0 ml/min. The detection was monitored at 410 nm under an UV detector (Hannauer et al, 2012).…”
Section: Purification Of Pyoverdinementioning
confidence: 99%
“…The assigned structures are illustrated in Figure 4BD. While the wild type strain produced the well-known pyoverdines PVD-α-ketoglutaric acid [2], PVDsuccinamide [3], and PVD-succinic acid [4], the data clearly showed that the pyoverdines of the pvdO deletion mutant were the known dihydrointermediates of the pyoverdines with the different modifications known for the first residue, namely glutamic acid [5], α-ketoglutaric acid [6], succinamide [7], and succinic acid [8]. The succinic acid form [8] was very low abundant, and some ferribactin [9] was detected in both preparations, especially in the pvdO deletion strain.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescent pseudomonads warrant their iron supply by pyoverdines, fluorescent siderophores that are derived from non-ribosomally synthesized peptides that are called ferribactins (2) (Figure 1). Ferribactins are transported into the periplasm in acylated form and deacylated thereafter by PvdQ (3)(4)(5). In the periplasm, a 5,6-dihydroxyquinoline fluorophore is generated from ferribactin and the conserved glutamic acid residue at the first position of the peptide is modified (6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%